Qin-Qiao-Xiao-Du formula alleviate influenza virus infectious pneumonia through regulation gut microbiota and metabolomics - Lian, Bo; He, Shasha; Jiang, Hui; Guo, Yuhong; Cui, Xuran; Jiang, Tao; Su, Rui; Chen, Yuehong; Zhao, Chunxia; Zhang, Mina; Hu, Yahui; Ye, Haoran; et al. (Frontiers in Medicine, 2022)
Qin-Qiao-Xiao-Du (QQXD), a traditional Chinese medicine formula, has been used in the clinical treatment of influenza virus pneumonia. However, the effects and mechanisms of QQXD on influenza virus pneumonia remain unknown. Therefore, this study explores the mechanisms of QQXD in the treatment of influenza virus pneumonia from the point of view of intestinal flora and metabolism. The results showed that QQXD was able to reduce mortality, weight loss, lung viral load, lung index and lung injury in influenza virus mice. A cytokine array found that the QQXD attenuated the expression of serum IL-1α, IL-4, IL-12(P70), and TNF-α. Subsequently, 16s rRNA gene sequencing showed that QQXD could increase the relative abundances of Gemmiger, Anaerofustis, Adlercreutzia and Streptococcus and decrease those of Dehalobacteriu, Burkholderia, Prevotella, Butyrimimonas, Delftia, and others. Meanwhile, targeted metabolic profiling analysis showed that QQXD could regulate nitrogen metabolism, phenylalanine metabolism, valine, leucine and isoleucine biosynthesis. Correlation analysis demonstrated that the regulatory effect of QQXD on the cyanoamino acid metabolism pathway was associated with changes in the abundance of Parabacteroides, Pediococcus and Clostridium in influenza mice. In conclusion, our study revealed that QQXD can inhibit influenza virus replication, suppress cytokine storms, and protect mice from influenza virus infection pneumonia. The mechanisms are likely to be related to improved gut microbiota dysbiosis, increased intestinal carbohydrate metabolism, and up-regulated cyanoamino acid metabolism pathways.